Pengaruh Lingkungan Kerja terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kabupaten Tanah Datar - Jayanti, Nur Putri; Syamsir, Syamsir (JESS (Journal of Education on Social Science); Vol 2 No 1 (2018): Social Issues in Public ServiceDO - 10.24036/jess/vol2-iss1/60, 2018)
Law No. 6/2014 state d  that the Village Government should be able to perform the task of managing village finances with a large budget and to provide accountability for the expenditure. The problems that occur red  in Tanah Datar were that the nagari treasurers were  less transparent about the nagari's financial management. The purpose of this study was t o analyze the influence of work environment on the performance of nagari apparatus  in managing nagari financ e . Th is study  use d  quantitative method. The population in this study consisted of  525 respondents and 227 of them were chosen  as sample determined  with  Slovin formula and p roportional r andom s ampling t echnique. The data were analyzed with linear regression. The result of th is study indicated  that simultaneously and partially the work environment ha d  significant effect s  on the performance of the nagari apparatus i n the management of nagari finance in Tanah Datar District .